Pertempuran Ideologi Desainer Grafis Modernisme dan Postmodernisme dalam Konteks Font Helvetica - Harnoko, Irwan (Humaniora, 2013)
This article discusses the mindset of modernism designers: Massimo Vignelli, Wim Crouwel as opposed to the perspective of postmodernism designers: Paula Scher and David Carson on Helvetica font. This discussion becomes interesting because the leaders of the two sides are the key figures in the world of graphic design. Their opinions on Helvetica font can be used as a guide to study world’s graphic design, due to they dominate the mindset of contemporary designers.